1992
DOI: 10.1093/bja/69.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Video Surveillance of Oxygen Administration by Mask in Postoperative Patients

Abstract: Patients may not receive prescribed oxygen because the oxygen face mask becomes displaced. Using video, we have observed the position of the face mask in 20 postoperative patients and recorded the timing and the events associated with mask displacement. Correct placement of the mask was confirmed at the start of the 8-h study period from 22:00 on the first night after operation. The mask remained on continuously and positioned correctly in only one patient. In the other 19 patients, it was removed 64 times (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The OxyArm had the best comfort score, independent of oxygen flow rate, presumably because of its oxygen premixing system. 5 Furthermore, Nolan et al 6 reported that a face mask is often removed for routine nursing tasks and that patients are frequently hypoxemic during these periods. It is also quite conceivable that the open-and microphone-type oxygen delivery systems tested in this study would have to be removed from the mouth/nose less frequently than would the other two devices tested.…”
Section: Méthodementioning
confidence: 99%
“…The OxyArm had the best comfort score, independent of oxygen flow rate, presumably because of its oxygen premixing system. 5 Furthermore, Nolan et al 6 reported that a face mask is often removed for routine nursing tasks and that patients are frequently hypoxemic during these periods. It is also quite conceivable that the open-and microphone-type oxygen delivery systems tested in this study would have to be removed from the mouth/nose less frequently than would the other two devices tested.…”
Section: Méthodementioning
confidence: 99%
“…In others, difficulties encountered during the use of oxygen delivery methods were reported. However, the evaluation period in these studies covered only the first night following the surgery (Nolan et al. 1992, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary exercises may decrease the incidence of respiratory complications. Oxygen therapy is effective at preventing hypoxaemia10 and would be titrated against oxygen saturation as measured by pulse oximetry. Continuous electrocardiographic monitoring, with computer assisted processing to detect abnormalities, would provide early warning of dysrhythmias and ischaemia.…”
mentioning
confidence: 99%